Analysis and determination of coupling efficiency and misalignment tolerances between a laser diode and a conically lensed fiber - Faidz, A. R.; Mishra, V. N. (2003)
In this paper, we present a simple analysis, utilising the ABCD transformation matrix method, to analyze and determine the coupling efficiency and misalignment tolerances between a laser diode and a conically lensed fibre. The calculated and measured results, that is, the coupling efficiencies and transverse misalignments, were compared for microlenses etched at 20, 30, and 40 min. The calculated results agree well with the measured values. The angular misalignments are also calculated to determine their tolerances. (C) 2004 Wiley Periodicals, Inc.